Clinical profile and outcome of viral encephalitis patients in a tertiary care hospital - N. N., Naseeb; Kumar, K. Shaji; A., Rajesh; John, Robin K.; George, David Jiju; Nizar, Ruksana (International Journal of Research in Medical Sciences, 2024)
Early detection and management of viral encephalitis patients presenting with various symptoms result in better outcomes. This study seeks to address gaps in timely diagnosis and management to reduce long-term neurological deficits. To study the clinical profile and outcomes of viral encephalitis patients admitted to a tertiary care hospital. Retrospective, observational study of 30 patients admitted at Travancore Medical College Hospital from April 2023 to May 2024. Fever, altered sensorium, and seizures were the most common presentations. Recovery was slower among immunocompromised patients, particularly those with chronic kidney disease. Common etiologies included Dengue, Herpes Simplex Virus (HSV), and Varicella Zoster Virus (VZV). Viral encephalitis remains a significant neurological emergency. Early recognition and management improve outcomes and reduce morbidity.